PERBANDINGAN METODE DESTRUKSI BASAH DAN DESTRUKSI KERING TERHADAP ANALISIS LOGAM BERAT TIMBAL (Pb) PADA TANAMAN RUMPUT BEBEK (Lemna minor) - Rusnawati Rusnawati; Bohari Yusuf; Alimuddin Alimuddin (PROSIDING SEMINAR KIMIA, 2018)
Research on analysis of Pb in duckweed plants (Lemna minor) has been conducted by comparing of wet and dry destruction method. The duckweed plants would be destructed in wet destruction and dry destruction used nitric acid and aquaregia by variation of time and temperature in wet destruction. The results of destruction were tested with an atomic absorption spectrophotometer. To see the comparative accuracy of this method is using recovery test (% R) to determine Pb by wet destruction gave the better result which it showed that with obtained of %R with the nitric acid in temperature 350°C and 1 hour of time were 99.09 % and aquaregia were 84.05 %. The values of %R in dry destruction by nitric acid and aquaregia were 79.96% and 75.31%. According to this research it can conclude that using the wet destruction is better than dry destruction. Keywords : Wet destruction, Dry destruction, Lemna minor, Recovery test, Atomoc Absorption Spectrophotometer.